Impact of financial behaviour on financial well-being: evidence among young adults in Malaysia - Sabri, Mohamad Fazli; Anthony, Mervin; Law, Siong Hook; Abdul Rahim@Abdul Wahab, Husniyah; Burhan, Nik Ahmad Sufian; Ithnin, Muslimah (Palgrave Macmillan, 2023)
The high cost of living and prolonged lockdowns due to the COVID-19 pandemic made the financial well-being of individuals vulnerable, especially young adults. This paper examines the impact of financial behaviour on financial well-being (FWB) among young Malaysians during the COVID-19 pandemic. The study collected variable data on financial literacy, financial behaviour, financial socialisation, self-control, financial technology and FWB. To collect a representative sample of Malaysian young adults, a multi-stage random sampling method was used, and 360 young adults aged 18–29 years old completed the questionnaires. Structural equation modelling was adopted to investigate the factors influencing young adults' FWB. The empirical findings revealed a significant mediating effect of financial behaviour in the relationships between financial literacy, financial socialisation, self-control, financial technology, and FWB. The research concluded that the mediation analysis yields a clear and firm conclusion that financial behaviour is important in empowering young adults’ FWB. Thus, the present study adds value to the existing literature on the relationship between financial behaviour and FWB. Furthermore, the paper’s findings will assist government agencies and non-governmental organisations in developing outreach programmes for young adults per the strategies outlined in the Twelfth Malaysia Plan and the aspirations pledged in the Malaysian Youth Policy 2015–2035.